Transforming Qur'anic Literacy Through Digital Pedagogy: Contemporary Innovations in Islamic Primary Education - Husna Husna (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This study examines how digital pedagogy contributes to improving Qur'anic literacy in contemporary Islamic primary education. A qualitative library research design was employed through a comprehensive review of scholarly literature concerning Qur'anic learning, educational technology, digital pedagogy, and Islamic primary education. The collected data were analyzed using thematic content analysis to identify emerging instructional innovations. The findings reveal that digital learning platforms, interactive mobile applications, gamification, multimedia instruction, and artificial intelligence-assisted feedback significantly improve students' motivation, engagement, pronunciation accuracy, and mastery of tajwīd. Nevertheless, successful implementation depends on teachers' digital competence and pedagogical readiness rather than technology alone. The study develops an integrated Digital Qur'anic Literacy Model that combines technological innovation with authentic teacher guidance and Islamic educational values. The novelty of this study lies in proposing a pedagogical framework that systematically integrates digital technology with traditional Qur'anic instruction while preserving the spiritual dimensions of Qur'anic learning